Employees experience and perceived environmental performance of malaysian chemical related industry - Yahya N.A.; Jaaffar A.H. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The previous research in environmental management practices suggests employees green behaviour can be regarded as one of the important assets for business environmental endeavours. Nevertheless there is lack study that focuses on Malaysian chemical related industries. This paper aims to explore the nexus between employees work experience, employees past environmental experience, and employees perceived environmental experience. 202 questionnaire were distributed through postal survey to manufacturing plant employees from eight chemical manufacturing industries from four regions in Malaysia including northern, central, east-coast, and southern. Data were analyzed using structural equation modelling at least the square.Based on the analysis, the study revealed that the employee's work experience has significant positive correlation with environmental performance that is seen by employees.Nevertheless employees past environmental experience was otherwise. This study has significant managerial implication for Malaysian chemical related industry by showing that how employees can be important assets for the company to minimize the impact of chemical related industry to the environment. BEIESP.